1999
DOI: 10.1148/radiology.210.2.r99fe21423
|View full text |Cite
|
Sign up to set email alerts
|

Occlusive Colon Carcinoma: Virtual Colonoscopy in the Preoperative Evaluation of the Proximal Colon

Abstract: Virtual colonoscopy is a feasible and useful method for evaluating the entire colon before surgery in patients with occlusive carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(103 citation statements)
references
References 30 publications
1
98
0
4
Order By: Relevance
“…It has been found that 1.5%-9.0% of patients with a colorectal carcinoma have a second carcinoma (59). In addition, 27%-55% of patients with a carcinoma have additional adenomatous polyps.…”
Section: Pre-operative Techniquementioning
confidence: 99%
“…It has been found that 1.5%-9.0% of patients with a colorectal carcinoma have a second carcinoma (59). In addition, 27%-55% of patients with a carcinoma have additional adenomatous polyps.…”
Section: Pre-operative Techniquementioning
confidence: 99%
“…(4) Evaluation of the entire colon and accurate preoperative staging are essential for the optimal treatment and surgical planning of colorectal cancers. This also helps to identify patients who may benefit from chemoradiation.…”
Section: Introductionmentioning
confidence: 99%
“…(4,10) While several studies have proven that CT colonography can be used to screen for colorectal cancer, (9)(10)(11) few studies have evaluated whether contrast-enhanced MDCT colonography (CEMDCTC) is valuable for preoperative staging of colorectal cancer. (9,11) The present study aimed to compare the accuracy of colorectal cancer staging done using CEMDCTC against that done using surgery and histopathology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations